The Coup: 1953, the CIA, and the Roots of Modern U.S.-Iranian Relations By Ervand Abrahamian (New York: The New Press, 2013. 277 pages.) (American Journal of Islam and Society, 2014)
In his most recent work, The Coup: 1953, the CIA, and the Roots of ModernU. S.-Iranian Relations, Ervand Abrahamian (Distinguished Professor of Iranianand Middle Eastern History, Baruch College of the City University, NewYork) recounts a definitive moment of modern Iranian history that overshadowsIranian-American relations to this day. Drawing on a remarkable varietyof sources – accessible Iranian official documents, the Foreign Office andState Department files, memoirs and biographies, newspaper articles publishedduring the crisis, recent Persian-language books published in Iran, aCIA report leaked in 2000 known as “the Wilber document,” and two contemporaryoral history projects (the Iranian Oral History Project at HarvardUniversity and the Iranian Left history project in Berlin) – the author providesa detailed and thorough account of the 1953 coup.Challenging the dominant consensus among academicians and politicalanalysts that the coup transpired because of the Cold War rivalries betweenthe West and the Soviet Union, he locates it within the paradigms of the clashbetween an old imperialism and a burgeoning nationalism. He then traces itsorigins to Iran’s struggle to nationalize its oil industry and the Anglo-Americanalliance against this effort.The book is divided into four chapters. The first chapter, “Oil Nationalization,”narrates the history of Iran’s oil industry and various encounters betweenthe Anglo-Iranian Oil Company (AIOC) and the Iranians. The Anglo-Persian Oil Company (APOC), an English company founded in 1908 followingthe discovery of a large oil field in Masjed Soleiman in southern Iran, wasrenamed AIOC in 1935. AIOC gradually turned into a vital British asset andprovided its treasury with more than £24 million a year in taxes and £92 millionin foreign exchange in the first decades of the twentieth century ...